Analisis Kinerja Struktur Gedung IGD Terpadu K.R.M.T Wongsonegoro Kota Semarang - TALITHA ZHAFIRA; Ilham Salman Ariq; Deva Eryan Sugya Mawada; Trias Widorini (Universitas Muhammadiyah Purwokerto, 2024)
According to its geographic location, Indonesia is part of a region prone to earthquakes, as it is situated at the convergence of three tectonic plates: Eurasian, Pacific, and Indo-Australian. These plates can collide at any time, resulting in tectonic earthquakes. Due to the occurrence of earthquakes inIndonesia, there are significant losses to buildings. Therefore, the developmentof earthquake analysis on structures is necessary. Spectrum response analysisis one of the methods used in this report, analyzing the relationship betweenthe structural period of buildings and the acceleration values experiencedduring earthquakes.This study focuses on the Integrated Emergency Room Building of K.R.M.TWongsonegoro Semarang, aiming to determine the building's safety level under seismic loads according to the Indonesian Earthquake Resilience Design Standard 1726;2019. The analysis includes base shear, displacement, and story drift values using the ETABS V.20 software. The analysis results indicate that the Integrated Emergency Room Building of K.R.M.T Wongsonegoro Semarang is considered safe, with a dynamic spectrum response base shear exceeding 100% of the static earthquake. The maximum displacement values obtained are 15.87 mm in the X direction and 19.08 mm in the Y direction, while the maximum story drift values are 21.64 mm in the X direction and25.24 mm in the Y direction, ensuring the building's safety against ultimate limit performance (0.02h).